Development Of Capacitive Composite Materials Using Alkaline Titanates And Kaolinite Clay - See, Alex (2009)

(untitled)
This research was designed to form a better dielectric composite material using one stable state dielectric matrix material and a good dielectric material as filler powder. The hypothesis is that the encapsulation of the filler powder by the matrix material, thus providing a bridge between the net polarizations of the composites. There are some limitations to the hypothesis, namely in the reactions and the limited control of the encapsulation process. Distinct dielectric composites were successfully produced using locally sourced kaolinite clay and chemically produced alkaline titanates for example, Barium Titanate (BT) and Strontium Titanate (ST). The samples were made using kaolinite as the base matrix and alkaline titanate added in varying ratios. The alkaline titanate were synthesized via solid-state reaction using a carbonate derivative of the alkaline cation and rutile titanium (IV) oxide sintered at 1200°C to 1300°C. White kaolinite was used to fuse the alkaline titanate material in varying weight ratios. The powders were dry-mixed and made into pellets for calcination at 1000°C. The XRD data of BT-kaolinite type composites revealed a chemical reaction between the matrix and the filler powder at various combinations. Thus, BT additives reacted with the mullite and silica components and produced celsian feldspar in the composite system. This suggests that the system polarization contains the sum of four interfacial polarization processes at different temperatures. ST-mullite composites showed distinct varying interfacial cladding and dipolar relaxation for all composites. SEM micrographs revealed fused and flaky parts formed in the BT composite samples whereby the powders were melted together. ST composite samples only showed inter-grain formation of the filler and matrix material. EDX, however, showed that there was some contamination in the matrix powder with potassium and carbon elements in the system. Dielectric properties for both BT and ST composites exhibited low dielectric constant values ranging from 10 to 20 in the frequency range 10 Hz to 1 MHz. Dielectric modelling showed that the BT composite samples displayed single relaxation processes for the sample series whereas the ST composite samples exhibited multiple thermally activated dielectric relaxations. The modelling of the dielectric data was done using the Havriliak-Negami equation to show two distinct dielectric processes occurring within the same framework. Impedance plots showed significant varied impedance based on the measured temperatures with both composite series exhibiting high resistance. DC conductivity measurements were carried out on the samples, yielding very high activation exothermic and endothermic activation of energy of reactions in the medium. Dielectric modulus plots, however showed varied dispersion due to deformations in dielectric stresses in the composite series. Microwave frequency measurements showed dielectric properties of the medium without the interfacial polarization